Cationized albumin conjugated solid lipid nanoparticles as vectors for delivery of albendazole against cystic echinococcosis - Fariba Faizi; Reza Mahjub; Negin Torabi; Seyedmousa Motavallihaghi; Mohammad Fallah (Parasites & Vectors)
Abstract Background Cystic echinococcosis (CE) is a common neglected parasitic disease. Nanoparticles containing drugs have been widely utilized in various formulations for several purposes, including improving the bioavailability of drugs by increasing the solubility and dissolution rate of the nanoparticles. The purpose of this study was to evaluate the effects of solid lipid nanoparticles containing albendazole and conjugated to albumin (B-SLN + ABZ) as a novel treatment approach for hydatid cysts in vivo. Methods Albendazole-loaded solid lipid nanoparticles were prepared by emulsification and solvent evaporation method. The experimental mice were assessed for prophylactic and therapeutic effects of the drugs. Ultrastructural changes were observed by transmission electron microscopy. Results The variance analysis of the fitted model indicated that the Glyceryl monostearate (GMS)/soy lecithin concentration ratio and the amount of albendazole had a significant effect on nanoparticle size. The GMS/soy lecithin concentration ratio and the amount of albendazole had a notable effect on nanoparticle polydispersity index (PdI) and entrapment efficiency (EE%), respectively. During chemoprophylaxis, the B-SLN + ABZ group showed a lower number and weight of cysts (0.90 ± 0.73 and 15.01 ± 10.46, respectively) compared with the ABZ + SLN group (1.4 ± 0.51 and 26.73 ± 9.92, respectively). In addition, therapeutic efficacy analysis showed a significant reduction in wet weights of metacestodes in mice treated with both B-SLN + ABZ (29.37 ± 13.82 mg) and SLN + ABZ (35.88 ± 7.49 mg) compared with the control group (59.78 ± 3.80 mg). Conclusions The results showed that B-SLN + ABZ nanoparticles were more effective against E. granulosus cysts compared with free ABZ. The cysts in the animals receiving B-SLN + ABZ every 24 h showed more ultrastructural changes. Graphical abstract